Principles of economics - Mankiw, N. Gregory (Fort Worth, TX : Dryden Press, 1998)
In writing this textbook, Mankiw tried to put himself in the position of someone coming to economics for the first time.This text is written for the students. The author wanted to bring economics to life for them and keep them interested in it. He has revealed to students how economics affects their everyday lives by building in a strong policy orientation to show them economics in "action".
Includes index.
oif 16/10/14
Loan
Keywords: Economics; Principles of Economics; Economics - Principles